Esta questão é de vezes ou de dividir? (Revista Cocar, 2017)
Este trabalho apresenta resultados de uma pesquisa que objetivou analisar os efeitos da elaboração da sentença natural do enunciado na escolha da operação e no desempenho da resolução na resolução de questões multiplicativas com as etapas de: revisão de estudos, pré-teste, elaboração da sequência didática, aplicação da sequência, pós-teste e análise dos resultados. A parte experimental ocorreu com 23 alunos de uma escola da rede municipal de Abaetetuba/PA. A comparação dos resultados dos pré- e pós-testes apontou aumento significativo do acerto no pós-teste, a análise do Coeficiente de Correlação Linear de Pearson revelou influencia ínfima dos fatores socioeconômicos nos resultados. Conclui-se que a construção da sentença matemática natural diminuiu a dificuldade da escolha da operação.Palavras-chave: Educação. Ensino de Matemática. Resolução de problemas multiplicativos. Escolha da operação.Is this question of multiplying or of dividing?This article presents the results of a research, whose goal was to analyze the effects of elaborating the natural sentence of the statement in the choice of the operation. And these same effects in the performance of the resolution in the resolution of multiplicative questions with the following steps: review of previous work, pre-test, elaboration of didactic sequence, application of the sequence, post-test and analysis of results. The experiment was conducted with 23 students of a city school in Abaetetuba/PA. The comparison between results of the pre- and post-tests showed a significant increase in the number of correct answers in the post-test, and an analysis of the Pearson Linear Correlation Coefficient revealed negligible influence of socioeconomic factors in the results. One concluded that the construction of the natural mathematical sentence decreased the difficulty of choosing the operation.Key words: Education. Mathematics Teaching. Resolution of multiplicative problems. Choice of operations.